Prenatal Development of Scapula, Humerus, Radius and Ulna in Sheep - Supriya, B.; Ramayya, P. Jagapathi; Dhyana, V. Reddy; Rao, T. S. Chandrasekhara (Indian Journal of Veterinary Anatomy, 2016)
The present study included the identification of chronological sequence of appearance of primary and secondary ossification centers and their development in scapula, humerus, radius and ulna of sheep. Forty-five sheep fetuses irrespective of sex were used for this study. Alizarin red and alizarin red with alcian blue methods, radiography techniques were used to detect the ossification centers at an early stage. In the present study the separate ossification centers for the corpus scuplae appeared at 45 days and tuber scpulae at 107 days. The corpus humeri showed ossification at 45 days, epiphysis distalis at 95 days,caput humeri at 97 days, tuberculum majus at 99 days, epicondylus medialis at122 daysand epicondylus lateralis at128days in sheep.The ossification centers for corpus radii, epiphysis distalis and caput radii were observed at 43 days, 94 days and95 days respectively. The ossification for corpus ulnae et caput ulnae and tuber olecraniat 43 days , 107 days respectively. Styloid process showed ossification at 128 days.